Search for axionlike particles produced in e+ e− collisions at Belle II - Abudinén, Fernando; Adachi, I.; Aihara, H.; Akopov, N.; Aloisio, A.; Ameli, F.; Anh Ky, N.; Asner, D. M.; Aushev, T.; Aushev, V.; Babu, V.; Baehr, S.; et al. (Physical review letters, 2020)
We present a search for the direct production of a light pseudoscalar 𝑎 decaying into two photons with the Belle II detector at the SuperKEKB collider. We search for the process 𝑒+⁢𝑒−→𝛾⁢𝑎, 𝑎→𝛾⁢𝛾 in the mass range 0.2<𝑚𝑎<9.7 GeV/⁢𝑐2 using data corresponding to an integrated luminosity of (445±3) pb−1. Light pseudoscalars interacting predominantly with standard model gauge bosons (so-called axionlike particles or ALPs) are frequently postulated in extensions of the standard model. We find no evidence for ALPs and set 95% confidence level upper limits on the coupling strength 𝑔𝑎⁢𝛾⁢𝛾 of ALPs to photons at the level of 10−3 GeV−1. The limits are the most restrictive to date for 0.2<𝑚𝑎<1 GeV/⁢𝑐2.
Im Titel ist die Eulersche Zahl als Symbol e dargestellt, das Plus- und Minuszeichen bei e hochgestellt
Gesehen am 19.09.2024